Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Batu Bara - Ullah Khan, Humera Asad (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to examine the effect of financial performance on firm value in the coal sector listed on the Indonesia Stock Exchange for the period 2017-2019. Financial performance in this study is represented by ROA (Return on Assets) and ROE (Return on Equity). Samples were taken using purposive sampling method, obtained 12 coal companies. The results of this study indicate that the ROA (Return on Asset) and ROE (Return on Equity) simultaneously have an effect on firm value. ROE (Return on Equity) partially affects firm value in the coal sector listed on the Indonesia Stock Exchange for the 2017-2019 period.